2013
DOI: 10.1007/s12639-013-0415-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hepatic antioxidant changes in ovine dicrocoeliosis

Abstract: Dicrocoeliosis, caused by Dicrocoelium dendriticum is a hepatic parasitic disease of clinical and financial significance in ruminant breeding, which causes direct losses due to condemnation of parasitized livers. The purpose of our study was to assess the effects of natural dicrocoeliosis on the antioxidant defence capability of the liver in sheep. For this purpose, livers of 40 infected sheep with D. dendriticum along with livers of 20 healthy (control) sheep were collected from animals slaughtered in Khuzest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…For example, using samples derived from blood or tissues, antioxidant biomarkers (such as Glutathione (GSH)) could be analyzed. The GSH content indicates the cell’s defense against ROS causing cellular injury [ 123 , 124 ] and reflecting the ability of a tissue to scavenge excess superoxide anions leading to oxidative stress [ 125 ], Malondialdehyde (MDA)-a direct indicator of cell membrane damage occurring in the tissue [ 126 , 127 ], Catalase (CAT)-an indicator of CH toleration by that particular tissue [ 128 ], Superoxide dismutase (SOD)-an indicator of the active enzyme involvement in neutralizing the effect of free radicals [ 129 ] and Level of protein content-an indicator of cell capacity of mitigating the effect of free radical and peroxide processes resulting in modulating the cellular antioxidant status [ 130 ]. Furthermore, other aspects, as below, are also concerned as described below [ 131 , 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, using samples derived from blood or tissues, antioxidant biomarkers (such as Glutathione (GSH)) could be analyzed. The GSH content indicates the cell’s defense against ROS causing cellular injury [ 123 , 124 ] and reflecting the ability of a tissue to scavenge excess superoxide anions leading to oxidative stress [ 125 ], Malondialdehyde (MDA)-a direct indicator of cell membrane damage occurring in the tissue [ 126 , 127 ], Catalase (CAT)-an indicator of CH toleration by that particular tissue [ 128 ], Superoxide dismutase (SOD)-an indicator of the active enzyme involvement in neutralizing the effect of free radicals [ 129 ] and Level of protein content-an indicator of cell capacity of mitigating the effect of free radical and peroxide processes resulting in modulating the cellular antioxidant status [ 130 ]. Furthermore, other aspects, as below, are also concerned as described below [ 131 , 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative damage results in structural alteration in membrane release of cell and organelle contents and essential fatty acids loss, which is seen with cytosolic aldehyde and peroxide product formation. The end product of free radical reactions on membrane fatty acids is called MDA (36). Free radicals have been reported to play a role in the pathogenesis of parasitic infections (10,11,36).…”
Section: Discussionmentioning
confidence: 99%
“…The end product of free radical reactions on membrane fatty acids is called MDA (36). Free radicals have been reported to play a role in the pathogenesis of parasitic infections (10,11,36). Many studies to date have reported increased blood concentrations of lipid peroxidation products during parasitic infections (14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant MDA decrease was observed due to lipid peroxidation which is a direct indicator that cell membrane damage has occurred in the tissue (Jonas et al, 2000;AshokKumar, 2004). Increased CAT observed in this study may indicate enhanced triherbal toleration by that particular tissue (Bahrami et al, 2015). Rise in SOD activities observed may indicate presence of active enzyme involvement in neutralizing the effect of free radicals (Deger et al, 2008).…”
Section: Discussionmentioning
confidence: 56%